Determinants of stock market performance in Malaysia / Anis Thuraya Aminuddin Shah and Anisa Razana Karya - Aminuddin Shah, Anis Thuraya; Karya, Anisa Razana (Faculty of Business and Management, 2019)
For years, the study of determinants for stock market performance are well-documented. However, most of the studies are focus on the macroeconomic factors in the developed country context. In light of this, this study intends to bright the gap by examining the determinants that affect the stock market performance in developing country namely Malaysia. More specifically, this study aims to extend the current literature reviews by including exchange rate, inflation rate, crude oil price, money supply and U.S. stock market performance in determining the relationships with the Malaysian stock market performance. By using Ordinary Least-Square regression method in E-views, multiple linear regression analysis is performed to examine the hypotheses and statistical relationships in a quarterly basis from quarter 1 of 1992 until quarter 4 of 2017. The results conclude that exchange rate, crude oil price has significant negative relationship with Malaysian stock market performance while money supply and U.S. stock have significant positive relationship with Malaysian stock market performance. On the other hand, this research also indicates that inflation variable have an insignificant negative relationship with Malaysian stock market performance. These result would give better understanding and should be useful for further studies, policymakers and investors.